Intralesional bleomycin sclerotherapy in childhood lymphangioma - Erikçi, Volkan; Hoşgör, Münevver; Yıldız, Melih; Örnek, Yılmazcan; Aksoy, Nail; Okur, Özkan; Demircan, Yusuf; Genişol, İncinur (The Turkish Journal of Pediatrics, 2013)
This clinical trial was conducted to evaluate the efficacy of intralesional bleomycin sclerotherapy (IBS) in children with lymphangioma and to determine the incidence of complications in the treatment. Seventeen lymphangioma cases were treated with IBS from 2004 to 2012. Age, mode of presentation, locations and types of lesions, and results of treatment were studied. Lymphangioma was diagnosed by physical examination and imaging studies. Most of the lesions were located in the cervical region (n=8) and of macrocystic type (n=13). After the first injection, three patients were lost to follow-up. Good response was seen in 50% of the lesions, complete resolution in 35.7%, and poor response in 14.3%. No serious complications or side effects were observed after IBS. The average follow-up was 18.5 months. IBS is effective in the treatment of lymphangioma. Although no major adverse effects have been encountered, complications should be kept in mind and in the event of their occurrence be treated immediately.